CLASSIFICATION OF CONFLICT SITUATIONS BETWEEN AIRCRAFT AND SELECTION OF DANGER ZONES - Харченко, В. П.; Кукуш, О. Г.; Бабак, Є. А.; Закора, С. А. (Proceedings of National Aviation University (archive), 2021)
The mathematical model of estimation of the shortest distance between trajectories of aircraft and formation of conflict situations depending on results of estimation is considered. Particular attention is paid to the construction of trajectories for two aircraft, finding the shortest distance between two trajectories of aircraft and the confidence interval for the shortest distance.